1996
DOI: 10.1518/001872096778827305
|View full text |Cite
|
Sign up to set email alerts
|

SPECIAL SECTION: Medication Instruction Design: Younger and Older Adult Schemas for Taking Medication

Abstract: We examined whether older and younger adults share a schema for taking medication and whether instructions are better recalled when they are organized to match this schema. Experiment 1 examined age difference in schema organization. Participants sorted medication items (e.g., purpose, dose, possible side effects) according to similarity and then ordered the items to create a preferred instruction set. Cluster analysis of the sort and order data showed that younger and older adults share a schema for taking me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
50
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 37 publications
6
50
0
Order By: Relevance
“…Morrow, Leirer, Andrassy, Decker, and Stine-Morrow (20) found the orderings by older adults and undergraduates concurred with those found in their first study (19) suggesting that people share similar schemas for prescription label components. According to Morrow et al (20), label ordering that is compatible with people's schema facilitates information acquisition.…”
Section: Label Component Prioritizationmentioning
confidence: 59%
See 1 more Smart Citation
“…Morrow, Leirer, Andrassy, Decker, and Stine-Morrow (20) found the orderings by older adults and undergraduates concurred with those found in their first study (19) suggesting that people share similar schemas for prescription label components. According to Morrow et al (20), label ordering that is compatible with people's schema facilitates information acquisition.…”
Section: Label Component Prioritizationmentioning
confidence: 59%
“…Morrow et al (19.20) suggest that these orderings reflect people's mental models of how to take medications, and proper use of relevant label information is likely to be facilitated when the design of drug labels accommodates consumer's preexisting cognitions (20). The Non-Prescription Drug Manufacturer Association (NDMA) recently recommended a standard label format for OTC medications to the FDA (10).…”
Section: Discussionmentioning
confidence: 99%
“…With increasing experience, older adults may develop a medication-taking schema that guides expectations about the information that should be provided by instructions. According to this schema, general information such as purpose should be followed by information about how to take the medication (e.g., dose and schedule), and then possible outcomes of taking the medication such as side effects (Morrow, Leirer, Andrassy, Tanke, & Stine-Morrow, 1996). We organized the instructions to match this schema because the order of information followed the schematic order.…”
mentioning
confidence: 99%
“…Studies investigating the effects of humanfactored instructions report that they are preferred (Klein & Meininger, 2004;Morrow et al, 1988;Morrow, Leirer, & Altieri, 1995), more understandable (Eustace, Johnson, & Gault, 1982;Morrell, Park, & Poon, 1989), and easier to memorize (Morrow et al, 1991(Morrow et al, , 1996, compared to a standard. Researchers have also suggested that apart from financial, educational, and psychosocial measures, applying human factors may play a role in increasing patient adherence (e.g., Boyle & Chambers, 2000;McDonald, Garg, & Haynes, 2002;Morrow et al, 2004;Murray et al, 2004;Park & Jones, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Patients categorize medication information into general identifying information (name, purpose), directions for use (dose, timing, warnings), and possible outcomes and side effects (see Morrow, Carver, Leirer, & Tanke, 2000;Morrow, Leirer, Altieri, & Tanke, 1991). Organizing information accordingly improves recall (Morrow, Leirer, Andrassy, Decker-Tanke, & Stine-Morrow, 1996). Presen-tation factors such as font, type size, contrast, and capitalization help organize information (Hartley, 1994a(Hartley, , 1994b.…”
Section: Introductionmentioning
confidence: 99%